Principles of econometrics - Theil, Henri (New York : Wiley, 1971)
This book describes the techniques available for economic data analysis. It examines a series of statistical models of increasing complexity. The book first summarizes the algebra and statistics prerequisites; it then presents the standard linear model of econometrics and various forms of residuals for testing the model$1 (Bs assumptions. The latter chapters develop such topics as the generalized least-squares method, simultaneous equation models, asymptotic distribution theory, and specification and aggregation analysis. The book is designed to be used both as a textbook for multilevel courses in econometrics and as a reference tool. s
Includes index.
Includes bibliographical references: p. 687-715.
rpm 28/06/2017
Loans
Keywords: Econometrics